SuPR-NaP Technique for Printing Ultrafine Silver Electrodes and its Use for Low-Voltage Operation of Organic Thin-Film Transistors. (3rd May 2018) - Kitahara, G.; Aoshima, K.; Tsutsumi, J.; Minemawari, H.; Arai, S.; Hasegawa, T.
ABSTRACT: Recently, an epoch-making printing technology called "SuPR-NaP (Surface Photo-Reactive Nanometal Printing)" that allows easy, high-speed, and large-area manufacturing of ultrafine silver wiring patterns has been developed. Here we demonstrate low-voltage operation of organic thin-film transistors (OTFTs) composed of printed source/drain electrodes that are produced by the SuPR-NaP technique. We utilize an ultrathin layer of perfluoropolymer, Cytop, that functions not only as a base layer for producing patterned reactive surface in the SuPR-NaP technique but also as an ultrathin gate dielectric layer of OTFTs. By the use of 22 nm-thick Cytop gate dielectric layer, we successfully operate polycrystalline pentacene OTFTs below 2 V with negligible hysteresis. We also observe the improvement of carrier injection by the surface modification of printed silver electrodes. We discuss that the SuPR-NaP technique allows the production of high-capacitance gate dielectric layers as well as high-resolution printed silver electrodes, which provides promising bases for producing practical active-matrix OTFT backplanes.